KEPEMIMPINAN TRANSFORMASIONAL KEPALA SEKOLAH DALAM MENGELOLA KEBERAGAMAN LATAR BELAKANG GURU DI SDIT MUTIARA HATI: PENDEKATAN HUMANIS DAN PENGEMBANGAN SUMBER DAYA MANUSIA (Az-Zaida: Jurnal Ilmu Multidisiplin, 2026)
This study is motivated by the challenges faced by school principals in managing the diversity of teachers’ backgrounds in Islamic Integrated Elementary Schools (SDIT), encompassing differences in formal education, teaching experience, personal character, communication style, and pedagogical approach. Such diversity potentially becomes a source of conflict and productivity barriers when not properly managed. The purpose of this research is to examine in depth how the SDIT principal applies transformational leadership in managing teacher diversity to improve educator performance and professionalism. The study employed a qualitative approach with a single case study design at SDIT Mutiara Hati. Data were collected through in-depth interviews, participatory observation, and documentation, and then analyzed thematically. The findings reveal that the principal applies four components of transformational leadership synergistically: idealized influence through role modeling of values and work ethic; inspirational motivation through warm and meaningful vision communication; intellectual stimulation through training, workshops, and academic supervision; and individualized consideration through adaptive personal guidance tailored to each teacher’s needs. Teacher background diversity is constructed as an institutional asset managed through a humanistic approach based on need fulfillment and individual appreciation. The dialectical integration of transformational leadership, humanistic approach, and human resource development proved effective in orchestrating diversity into professional harmony that comprehensively enhances the quality of lesson planning, implementation, and evaluation at SDIT Mutiara Hati.